Behaviour of steel fibers reinforced exterior beam-column joint using headed bars under reverse cyclic loading. (October 2021) - Sachdeva, Payal; Danie Roy, A.B.; Kwatra, Naveen
Abstract: Fiber-reinforced cementitious composites have been increasingly used during recent years on beam-column joints and the introduction of headed bars is a practical solution to eliminate the congestion problem caused by hooked bars in beam-column joints. The present study emphasizes the evaluation of the performance of steel fiber reinforced concrete (SFRC) external beam-column joints (BCJ) using headed bars as an anchorage mechanism and the comparison has been made with the conventional bars which have been detailed in accordance with ACI 318-19 and ACI 352R-02. The repository of previous BCJ work has been further expanded by researching the effect of structural parameters i.e. compressive strength (C20 and C40) and steel fibers (1 and 1.5%) on the hysteresis curve, ductility, stiffness, energy dissipation, and cracking on all specimens. The experimental results have revealed that the headed bars can be significantly replaced by the conventional bars for the areas vulnerable to earthquakes due to their higher load carrying capacity with better ductility and stiffness response and reducing congestion in BCJ.